Key Success Factors of an E-Learning Course - Sylwia Kossakowska-Pisarek (Center for Open and Multimedia Eduacation of the University of Warsaw, 2012)
The article focuses on key success factors of an e-learning course based on the experience from a pilot course Effective Business Communication. It advocates the need to concentrate on specific key areas when assessing an e-learning course. These areas are vital for an appropriate preparation and conducting of an e-learning course and comprise among others fostering collaboration between participants, supporting autonomy and reflection on the process of learning and developing learners' community.